An Error Analysis Of Undergraduate Students’ English Pronunciation - Faradila Mesfer; Muhammad Yahrif; Suharti Siradjuddin (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2024)
English Pronunciation error cannot be underestimated. Especially for students who majoring English in Higher Education. Thus, the purpose of this research was to find out the types of pronunciation Error which were consonant and vowel sounds made by the second semester students of English Education Department of Megarezky University based on surface strategy taxonomy and the dominant errors between vowels and consonants. The research design was descriptive qualitative with a focuse on pronunciation errors. The result of this study indicate that there were 70 errors made by the second semester students while reading aloud an english short text. It was found 37 errors on pronouncing vowels (52.85%) and 33 errors on pronuncing consonants (47.14%) in the linguistics category. While, there were 5 omission errors (7.14%), 8 addition errors (11.42%), 48 misformation errors (68.57%), and 9 misordering errors (12.85%) in the surface strategy taxonomy. It can be concluded that the pronunciation errors were made by the second semester students of English Education Department of Megarezky University namely, pronunciation and errors based on linguistic catogery taxonomy is a misformation errors.